The development dynamics and spreading peculiarities of the pathological process in the retroperitonael space in acute pancreatitis - V. V. Ganzhy; I. P. Kolesnyk; N. A. Yareshko; A. I. Marusiy (Patologìâ)
Despite rapid development of medicine, acute pancreatitis (AP) is still a problem.